Anti-OLA1 autoantibody is a potential early diagnostic marker for hepatocellular carcinoma - Xiong, Wenzhuo; Duan, Xuehui; Dai, Liping; Wang, Peng; Ye, Hua; Shi, Jianxiang; Wang, Keyan (Frontiers in Immunology, 2025)
BackgroundEarly detection of hepatocellular carcinoma (HCC) enhances survival outcomes. Tumor-associated autoantibodies demonstrate early emergence during carcinogenesis, offering potential as non-invasive diagnostic biomarkers. This multicenter study aims to evaluate the diagnostic value of anti-OLA1 autoantibody in HCC.MethodsProtein microarray was used to screen for autoantibodies in AFP - negative patients with HCC (ANHCC) and normal controls (NC) during the discovery stage. In the validation stage, 413 HCC patients and 655 control from three centers were recruited to evaluate anti-OLA1 autoantibody performance using enzyme-linked immunosorbent assay. Receiver Operating Characteristic (ROC) curve analysis and area under the curve (AUC) were used to assess its diagnostic value. Anti-OLA1 autoantibody was combined with liver function parameters in a logistic regression model to improve HCC diagnosis. Finally, OLA1 expression, immune infiltration, and prognostic impact were analyzed using public databases.ResultsAnti-OLA1 autoantibody was identified by protein microarray with an AUC of 0.75 for distinguishing ANHCC from NC. Multi-center validation confirmed these results, showing AUCs from 0.607 to 0.713 and sensitivity from 18.8% to 35.2%. Incorporating liver function parameters significantly improved diagnostic efficiency, with a net reclassification index of 1.04 and an integrated discrimination index of 0.46 in Zhengzhou, validated by an AUC of 0.93 in Nanchang. Public database analysis revealed OLA1 overexpression in HCC tissues correlates with increased immune cell infiltration and predicts poor early prognosis (P < 0.05).ConclusionAnti-OLA1 autoantibody shows promise as a serological HCC biomarker, with diagnostic performance significantly enhanced through combination with routine liver function parameters.